La vita di Romylos da Vidin asceta nei Balcani (1310 ca.-1376/1380) - Rigo, Antonio (Subsidia hagiographica, 2022)
"Romylos, originally called Rajko, was born in Vidin (a town on the southern bank of the Danube in Bulgaria) around 1310 into a Byzantine-Bulgarian family and died in the monastery of Ravanica (Serbia) around 1380. He was one of the most brilliant followers of the Hesychast tradition in the Eastern Orthodox Church in the 14th century. The monk Romylos, like many other Bulgarian monks, emigrated to neighbouring Orthodox countries: he stayed successively in Tarnovo, Paroria, Mount Athos, and finally in Valona and Ravanica. His tomb can still be seen in the church of the monastery in Ravanica. The Life of Romylos was written in Greek during the 1380's by Gregory, one of his disciples on Mount Athos; there is also a Slavonic translation of the text. The Life recounts Romylos' journey to the Balkans, and is one of the main sources documenting the famous 'school' founded by Gregory the Sinaitic in Paroria. The new Subsidia Hagiographica contains the critical edition of the Greek text (with Italian translation) and the Slavonic text. The book is destined to become the reference work for anyone interested in St Romylos and the religious history of the Balkans in the 14th century."--